Selection of local swamp rice cultivars from Kalimantan (Indonesia) tolerant to iron stress during vegetative stage - Vina Novianti; Didik Indradewa; Maryani MARYANI; Diah Rachmawati (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Novianti V, Indradewa D, Maryani, Rachmawati D. 2020. Selection of local swamp rice cultivars from Kalimantan (Indonesia) tolerant to iron stress during vegetative stage. Biodiversitas 21: 5595-5606. Kalimantan with the large swamp area is a potential region in Indonesia to develop local rice cultivars with high tolerance to iron toxicity in tidal lowlands. This research was conducted to select iron toxicity-tolerant in local Kalimantan-rice cultivars, namely: Amas (AMS), Pandan Ungu (PDU), Kambang (KMB), Suatek Merah (SM), Siam Unus Mayang (SUM), Siam Unus Kuning (SUK), and Siam 11 Panjang (S11P). As control, two rice cultivars: Ciherang (iron toxicity-susceptible) and Inpara 5 (iron toxicity-tolerant) were also used. The seeds were grown hydroponically for 35 DAP (days after planting) in Yoshida nutrient solution containing 0 ppm (control), 100 ppm (low), and 400 ppm (high) FeS2 as pyrite treatments. Morphological analysis (plant height, leaf length and width, and leaves number) showed that PDU and KMB cultivars have better characters for tolerating iron toxicity. The highest level of chlorophyll and carotenoid contents during iron toxicity treatment was observed in KMB cultivar. AMS cultivar had the highest proline level under high iron stress. Antioxidant enzyme analysis showed that AMS, PDU, and KMB cultivars had a high percentage increase in the activity of superoxide dismutase (SOD), hydrogen peroxide (H2O2), and ascorbate peroxidase (APX) enzymes when exposed to high pyrite conditions. Based on morphophysiological characteristics, biochemical component, and enzymatic antioxidant activity, it can be concluded that AMS, PDU, and KMB cultivars are potential candidates as iron toxicity-tolerant rice.